Pengembangan Metode Teknik Sterilisasi Eksplan Guna Meningkatkan Keberhasilan Kultur Jaringan Tanaman Stevia (Stevia Rebaudiana Bertoni) - Cahyono, Eko Hadi; Riani Ningsih (Politeknik Negeri Jember, 2023)
Stevia rebaudiana Bert is a shrub native to the borders of Paraguay, Brazil and Argentina. The leaves of this plant produce steviol glycosides, a secondary metabolite which has a sweetness level of 200-300 times sweeter than sugarcane sucrose. Conventional stevia propagation methods cannot meet the increasing need for stevia seeds or seedlings. Tissue culture is able to fulfill this deficiency because it has the potential to produce large amounts of uniform plantlets. Tissue Culture Technique is a vegetative propagation of plants. Tissue culture includes the cultivation of cells or cell aggregates, tissues and organs of plants in a medium containing sugars, vitamins, amino acids, organic salts, water, growth regulators and compacting agents. The composition of the growing medium is also very beneficial for the growth of fungi and bacteria. Therefore, explant sterilization is an important factor in determining the success of a tissue culture program. The problem is that until now there is no optimal explant sterilization technique for Stevia tissue culture. The aim of this research is to find out the best explant sterilization method from a combination of several disinfectants on Stevia (Stevia rebaudiana Bertoni) explants which can remove contaminants on the explants. The main parameters observed were Source of Contamination (descriptive: shape and color), Percentage of Explants Alive, Percentage of Contamination, Percentage of Browning, and Time when contamination first appeared (Early). The results showed that the sterilization method F used running water, immersion in detergent for 10 minutes, immersion in 1.5% fungicide solution and 1.5% bactericide for 10 minutes, 70% alcohol immersion for 1 minute, 0.05% HgCl2 immersion 3 minutes and immersion in 10% and 5% NaOCl respectively for 5 minutes had the lowest contamination percentage of 20% and the highest survival presentation of 80% with 80% fungal and 20% bacterial contaminants and the initial contamination occurred in the first week of observation.